2011
DOI: 10.3945/jn.109.114405
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast Frequency and Quality May Affect Glycemia and Appetite in Adults and Children

Abstract: Observational studies of breakfast frequency in children and adults suggest an inverse (protective) association between the frequency of eating breakfast and the risk for obesity and chronic diseases such as type 2 diabetes. More prospective studies with stronger designs are needed, as are experimental studies on this topic. In addition, above and beyond breakfast frequency, the roles of dietary quality and composition need to be studied in the context of eating or skipping breakfast. Experimental studies are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
110
1
19

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(136 citation statements)
references
References 54 publications
6
110
1
19
Order By: Relevance
“…In agreement with other studies 6,7,10 , the present study found an association between not smoking and breakfasting frequently. Smoking may reduce appetite in the morning and encourage the smoker to skip this meal 7 .…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In agreement with other studies 6,7,10 , the present study found an association between not smoking and breakfasting frequently. Smoking may reduce appetite in the morning and encourage the smoker to skip this meal 7 .…”
Section: Discussionsupporting
confidence: 83%
“…There are only a few studies that approach the factors associated with skipping breakfast. In general, they report a positive association between breakfasting and healthy lifestyles, such as not smoking, being physically active, controlling body weight and avoiding alcoholic beverages 3,6,7,10,24 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations